Literature in the Evolutionary Framework:: Darwin’s Theory of Evolution in English Literary Analysis - Sophonpanich, Rawitawan (Journal of Letters, 2024)
This article aims to examine the role of Charles Darwin’s theory of evolution in literature, considering its influence on Victorian writers—particularly in the realist novels of Charles Dickens and George Eliot—and extending to the emergence of evolutionary literary theory in the 20th century. The author applies this theory to analyze John Milton’s Sonnet 7. The analysis results demonstrate that Darwinian evolutionary literary theory has strengths in explaining character behavior through the lens of adaptation for survival but is limited by its neglect of historical and cultural contexts. The experimental reading of Milton’s Sonnet 7 clearly reflects this limitation, as the theory fails to comprehensively explain the religious and spiritual dimensions of the poem. However, this study suggests that Darwinian evolutionary literary theory can be a useful supplementary tool in literary analysis but should be used in conjunction with other critical methods to achieve a more complete understanding.